Unveiling the power of data in bidirectional charging: A qualitative stakeholder approach exploring the potential and challenges of V2G - Jan Lukas Demuth; Johannes Buberger; Annsophie Huber; Emma Behrens; Manuel Kuder; Thomas Weyh (Green Energy and Intelligent Transportation)
The increasing energy demand caused by digitalization, the integration of renewable energy sources, and the growing adoption of electric vehicles (EVs) pose significant challenges to power grids. The Vehicle-to-Grid (V2G) technology emerges as a solution that provides cost-effective energy storage capacities to address these challenges. This paper explores the roles, potentials, and challenges for the stakeholders involved in a V2G architecture. These include Consumers, V2G Systems, Power Markets, and V2G Communication operators. A major emphasis is on the importance of data in a bidirectional charging environment. Through a comprehensive literature research and in-depth interviews with 16 V2G experts, we identify the current state, research gaps, and insights related to V2G. In particular, we focus on addressing the challenges in a V2G architecture. Our analysis reveals evolving stakeholder roles, the potential for cost benefits and new revenue streams, and challenges related to costs, functionality, legal aspects, and market collaboration. Additionally, we highlight behavioral shifts among consumers and the crucial role of data collection, utilization, and sharing. This study contributes to V2G research by offering insights into customer adoption challenges, the extension of charging infrastructure, the importance of software and machine learning tools, and the need for grid player collaboration.